Inhibition of related JAK/STAT pathways with molecular targeted drugs shows strong synergy with ruxolitinib in chronic myeloproliferative neoplasm. (5th April 2013) - Barrio, Santiago; Gallardo, Miguel; Arenas, Alicia; Ayala, Rosa; Rapado, Inmaculada; Rueda, Daniel; Jimenez, Ana; Albizua, Enriqueta; Burgaleta, Carmen; Gilsanz, Florinda; Martinez‐Lopez, Joaquin
Summary: This study aimed to assess the antitumour effects, molecular mechanisms of action, and potential synergy of ruxolitinib with sorafenib, KNK437, dasatinib, and perifosine, in Philadelphia‐negative chronic myeloproliferative neoplasms (MPN). Cytotoxic and cytostatic effects of the different compounds were determined in the JAK2 V617F‐positive cell lines, HEL and Ba/F3 JAK2V617F EPOR, and in primary mononuclear and bone marrow CD34‐positive cells from 19 MPN patients. Ruxolitinib [50% inhibitory concentration (IC50 ) PV = 15 nmol/l], as well as sorafenib ( IC 50 PV = 8 μ mol / l ), KNK437 ( IC 50 PV = 100 μ mol / l ), and perifosine ( IC 50 PV = 15 μ mol / l ), were able to inhibit proliferation in cell line models and in primary cells from MPN patients. Dasatinib, KNK437, and sorafenib showed a strong synergistic effect in combination with ruxolitinib [combination index (CI) PV < 0·3]. Western blot confirmed that ruxolitinib blocked ERK, and consequently STAT5 activation, sorafenib inhibited ERK, P38 and STAT5, dasatinib blocked SRC and STAT5, and KNK437 decreased the stability of the JAK2 protein, reducing its expression. Inhibiting JAK2‐related proliferative pathways has the potential to inhibit cell proliferation in MPNs. Furthermore, the combination of ruxolitinib with inhibitors that target these pathways has a strong synergistic effect, which may be due to decreased activation of the common effector, STAT5.